Wealth Accumulation: The Influence of Certain Types of Financial Literacy and Moderated Islamic Spiritual Intelligence - Khilmatun Nafisah; Ananda Setiawan (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to examine whether several types of financial literacy, namely deposit literacy, risk literacy and debt literacy  affect on wealth accumulation, with Islamic spiritual intelligence as a moderating variabel. Respondents in this study were 200 households in Magelang City and Magelang Regency. Through multiple linear regression test and MRA tests, it is known that deposit literacy, risk literacy and debt literacy  have a significant effect on wealth accumulation. Furthermore, the Islamic spiritual intelligence is able to strengthen unsignificantly the influence of deposit literacy and debt literacy  on wealth accumulation. Meanwhile, the influence of risk literacy to wealth accumulation is weaken significantly by Islamic spiritual intelligence. This indicates the importance of financial literasy to grow up wealth accumulation